PROSPECTS FOR LIBERALIZATION OF THE COMPULSORY INSURANCE MARKET AND OPENING FOR INTERNATIONAL INSURANCE COMPANIES IN UZBEKISTAN (International journal of artificial intelligence, 2025)
This article examines the liberalization of the compulsory insurance segment in Uzbekistan's insurance market and its opening to international companies. Based on literature analysis, the study explores international experience in market liberalization and opportunities in the Uzbekistan context. As a result, gradual market liberalization and necessary conditions for foreign insurance companies' entry are proposed.